Rancang Bangun Aplikasi Informasi Penggunaan Laboratorium Prodi Sistem Informasi pada Fakultas Sains dan Teknologi UIN Alauddin Makassar - hartono, Nahrun; Mahfud Hidayat B; Rizaldy, Adhy (Jurnal INSYPRO (Information System and Processing), 2023)
The delivery process of laboratory usage information in the Information Systems Study Program at the Faculty of Science and Technology, UIN Alauddin Makassar, has not yet been computerized. The frequent changes in practicum schedules or laboratory usage have caused confusion among students in finding the appropriate laboratory for their practical activities. Additionally, the lack of a definite schedule makes it challenging for both students and lecturers to find available laboratories. This research aims to design and develop an application for laboratory usage information in the Information Systems Study Program at the Faculty of Science and Technology, UIN Alauddin Makassar. The application is expected to facilitate users in accessing information about laboratory availability and dynamically present the information according to their needs. After conducting user acceptance tests, where users were involved in providing questionnaires to evaluate the developed application, the results showed a usability percentage of 85% based on varying user perceptions. This indicates that the application performs excellently in providing services to its users.